'VALIANT ENGLISHMAN' christopher bethell, montshiwa's barolong and the bechuanaland wars,... 1878-1886. - Manson, Andrew, 1948- ([S.l.] : ROUTLEDGE, 2023)
This book describes the career of an English aristocrat, Christopher Bethell, who arrives in southern Africa in 1878 as the classic "remittance" man, despatched to the colonies to avoid a scandal at home. Bethell, an intelligence officer and later, a border agent, is the protagonist who facilitated the acquisition of arms for Montshiwa's Ratshidi-Barolong to resist the depredations of freebooters, mercenaries based mostly in the Transvaal. In his alliance with Kgosi Montshiwa Tawana, Bethell identifies with Kgosi Montshiwa's struggle to maintain political independence and economic security. The alliance was further cemented by Bethell's marriage to a Morolong woman Tepo Boapile - an unusual occurrence in nineteenth century southern Africa. Surrounded by aggressive freebooters from across their eastern border with the Transvaal and the ambiguous forces of colonial advancement from the Cape colony and Britain, Montshiwa and Bethell form an unlikely but enduring relationship aimed at safeguarding Rolong interests. As the Bechuanaland Wars of the early to mid-1880s intensify in brutality Montshiwa and his Chief of Staff, Christopher Bethell are forced to desperate measures to defend the Rolong and avoid outright dispossession. Bethell's demise is the trigger for firm British imperial intervention, the securing of the Road to the North and events that will determine the fate of Africans in south and central Africa. The book is a reminder that, in the author's words, "past relations between South Africa's different races were characterised as much by collusion and collaboration as they were by hostility, friction and dissent."
Keywords: Bethell, Christopher, -- 1856-1884; Rolong (African people) -- History; Africa, Southern -- History -- To 1899.; HISTORY / General; HISTORY / Africa / South / General; Africa, Southern -- History, Military